2003
DOI: 10.1213/01.ane.0000052380.69541.d4
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular Nerve Block Prolongs Analgesia After Nonarthroscopic Shoulder Surgery but Does Not Improve Outcome

Abstract: When used as an adjunct to an interscalene block combined with general anesthesia, suprascapular nerve block with bupivacaine moderately prolongs analgesia without improving other outcome measures after ambulatory nonarthroscopic shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 11 publications
3
44
0
2
Order By: Relevance
“…Similarly Neal et al 19 observed mean duration to be 220 min (3.67 h) in SSB group. Ritchie et al, 3 demonstrated that in the immediate post-operative period, a 51% reduction in demand and a 31% reduction in consumption of morphine delivered by a patient-controlled analgesic system in SSB group compared placebo group.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly Neal et al 19 observed mean duration to be 220 min (3.67 h) in SSB group. Ritchie et al, 3 demonstrated that in the immediate post-operative period, a 51% reduction in demand and a 31% reduction in consumption of morphine delivered by a patient-controlled analgesic system in SSB group compared placebo group.…”
Section: Discussionmentioning
confidence: 70%
“…(1:200,000), 15) 0.25% bupivacaine과 epinephrine 5 mg/ml, 16) 0.25% bupivacaine과 epinephrine (1:200,000), 17) 0.5% bupivacaine, 18) 1% ropivacaine, 19) 0.5% ropivacaine과 epinephrine (1:200,000), 20) 0.5% …”
mentioning
confidence: 99%
“…Control the pain is one of the main problems in those surgeries, since these procedures are associated with postoperative pain of great intensity and hard to be controlled 8,9 . Among the techniques more commonly employed for this purpose are the use of intravenous opioids associated or not with NSAIDs, the use of articular local anesthetic, suprascapular nerve block and cervical and brachial plexus blocks [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Among such techniques, brachial plexus block offers the best results on the analgesia 1,[3][4][5][20][21] .…”
Section: Discussionmentioning
confidence: 99%